Հնչակյան կուսակցությունն Առաջին համաշխարհային պատերազմի նախօրյակին - Մանուկ Ստեփանյան (ՀՀ ԳԱՍ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
Накануне Первой мировой войны в Западной Армении и во всех армянских поселениях Турции положение армян стало крайне невыносимым. Продолжая антиармянскую политику Абдула Гамида II, младотурецкие правители организовали и осуществили новые массовые истребления западных армян. По характеристике известного немецкого востоковеда Э. Вернера, истребление более 30-ти тысяч армян в Адане "явилось главной репетицией геноцида армян". On the eve of World War I the situation of Armenians became still more intolerable in all areas of Western Armenia and Turkey inhabited by Armenians. Continuing Abdul Hamid's policy of Armenian depressions the Young Turk leaders organized and executed new massacre of Western Armenians. As described by German well-known orientalist E. Werner, massacre of more than 30 thousands Armenians" became the general rehearsal of the genocide of Western Armenians".
Keywords: Պատմագրություն; Հայոց ցեղասպանություն (1915)